2001
DOI: 10.1161/01.cir.103.11.1515
|View full text |Cite
|
Sign up to set email alerts
|

Human Tissue Valves in Aortic Position

Abstract: Subcoronary implantation has a learning curve, resulting in more initial aortic regurgitation and early reoperation compared with root replacement. In both techniques, progression of aortic regurgitation over time is small but accelerated in young adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…This root replacement technique (RRT) decreases the risks of geometrical distortion due to technical error since the homograft is implanted as a functional unit. The sub coronary technique (ST) carries the advantage of an easier reoperation in the event of structural deterioration as compared to the RRT (24). However, the technique is difficult, has a learning curve, and the technique itself has a higher incidence of early reoperation risks if the exact geometry is not maintained.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This root replacement technique (RRT) decreases the risks of geometrical distortion due to technical error since the homograft is implanted as a functional unit. The sub coronary technique (ST) carries the advantage of an easier reoperation in the event of structural deterioration as compared to the RRT (24). However, the technique is difficult, has a learning curve, and the technique itself has a higher incidence of early reoperation risks if the exact geometry is not maintained.…”
Section: Discussionmentioning
confidence: 99%
“…However, the technique is difficult, has a learning curve, and the technique itself has a higher incidence of early reoperation risks if the exact geometry is not maintained. Willems and colleagues showed that the learning curve associated with ST is a major reason for early reoperation (24). RRT is easier to perform but reoperations after this technique are difficult.…”
Section: Discussionmentioning
confidence: 99%